Adaptive Fuzzy Event-Triggered Sliding Mode Control for Uncertain Euler-lagrange Systems With Performance Specifications - Wu, Yang; Yang, Xixiang; Yan, Huaicheng; Chadli, Mohammed; Wang, Yueying (IEEE transactions on fuzzy systems, 2023)
This work addresses the design of an event-triggered finite-time singularity-free terminal sliding mode control (SMC) algorithm for tracking of Euler-Lagrange (EL) systems subject to state/error constraints, unstructured dynamics, and external disturbances. First, a novel sliding mode manifold (SMM), not only devoted to the finite-time convergence of tracking errors to a small residual set around zero but also ensuring stringent constraint requirements, is proposed. The SMM is available for both constrained and unconstrained EL systems in a unified manner with no structural changes. Then, a fuzzy logic system (FLS) is introduced to dynamically compensate for uncertainties in the system. An extra robustifying term is added to the training policy to accelerate online learning. Also, an event-triggered mechanism is integrated into the tracker design procedure to reduce the frequency of signal transmission. Stability analysis proves that all closed-loop signals are uniformly bounded, and numerical simulations further illustrate the theoretical findings.